Evaluating the Usability of Virtual Tour Application Using the System Usability Scale (SUS) Method - Nur Cahyo Wibowo; Tri Lathif Mardi Suryanto; Mu'tasim Billah; Fajar Annas (IJCONSIST JOURNALS, 2022)
UPN "Veteran" Jawa Timur Virtual Tour is a campus virtual application that offers digital information about the university's buildings, rooms, and facilities. It is required to examine usability in order to determine whether the virtual campus tour of UPN "Veteran" Jawa Timur is useful to students. Numerous issues were discovered in the virtual campus tour of UPN "Veteran" Jawa Timur based on observational research by several students. users-friendly The System Usability Scale is a technique for evaluating information systems that involves end users and looks at three aspects: adjective rating, grade scale, and acceptability. Ten statement items are employed as an evaluation measure in the process of evaluating the usability scale system. The ultimate outcome of the evaluation was a 64 on a scale of one to ten. According to these criteria, the Virtual Tour of UPN "Veteran" Jawa Timur belongs to the high adjective rating group, group D on the grading scale, and group good on the acceptability scale. If the Virtual of UPN "Veteran" Jawa Timur Tour is still used, it can be stated that the usability component of the virtual tour has to be improved.